MENINGKATKAN PARTISIPASI PESERTA DIDIK MELALUI GAME-BASED LEARNING “KAHOOT” PADA PEMBELAJARAN BAHASA INGGRIS - Septi Sundari; Benny Prasetiya (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study is an action research aimed at improving participation and motivation among Grade IV B students at SDN Pegirian II/495 Surabaya in learning English through the use of the game-based learning platform